PENGARUH PENGELOLAAN PIUTANG TERHADAP EFEKTIVITAS ARUS KAS PADA PT. SATRIA LESTARI MULTI - Muhammad Rivandi; Gina Septiana (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2020)
The effectiveness of cash flow is effective cash management requiring a control to protect cash from losses due to theft or fraud. The purpose of the study was to determine the effect of debt management on the effectiveness of cash flows at PT. Satria lestari Multi. The object in this study is PT. Satria lestari Multi. The number of samples in this study were 48 samples starting from January 2016 to December 2019. The statistical test used was using a simple linear regression test. Based on the partial t test with a significance value of 0,000 <alpha 0.05 it can be concluded that debt management has a positive and significant effect on the effectiveness of cash flows.